Reseña de: Martín Marcos, David, People of the Iberian Borderlands. Community and Conflict between Spain and Portugal - Jorge Díaz Ceballos (Espacio, Tiempo y Forma. Serie IV, Historia Moderna)
Reseña de: Martín Marcos, David, People of the Iberian Borderlands. Community and Conflict between Spain and Portugal, 1640-1715, New York, Routledge, 2023, 292 págs. ISBN: 9780367758219